2021
DOI: 10.3390/pediatric13020030
|View full text |Cite
|
Sign up to set email alerts
|

Parent Training and Therapy in Children with Autism

Abstract: With the introduction of the Diagnostic and Statistical Manual of Mental Disorders-5th ed. (DSM-5) autism spectrum disorders (ASD) fall into the category of neurodevelopmental disorders. ASD is characterized by the inhibitory mechanisms responsible for social adaptation and emotional expression being underdeveloped, causing a child’s recognition and understanding of emotions to be impaired. Our study hypothesizes that early intervention using behavioral interventions such as Applied Behavior Analysis (ABA) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…In our study, the depressive symptoms assessed using the Beck Depression Inventory (BDI) and mentalization processes: they showed that parents who were able to make sense of both their own mental state and that of their child can serve as a protective factor for the child's development even in atypical developmental situations such as in ASD (Frolli et al, 2021). In our view, it is not only parents of children with ASD who may benefit from this type of training, but also the adult development (reflective functioning, mentalizing) of the individuals themselves, if this was not done earlier in their lives.…”
Section: Clinical Relevance and Therapeutic Implicationsmentioning
confidence: 87%
“…In our study, the depressive symptoms assessed using the Beck Depression Inventory (BDI) and mentalization processes: they showed that parents who were able to make sense of both their own mental state and that of their child can serve as a protective factor for the child's development even in atypical developmental situations such as in ASD (Frolli et al, 2021). In our view, it is not only parents of children with ASD who may benefit from this type of training, but also the adult development (reflective functioning, mentalizing) of the individuals themselves, if this was not done earlier in their lives.…”
Section: Clinical Relevance and Therapeutic Implicationsmentioning
confidence: 87%
“…Data analyses were performed with SPSS 26.0 [ 3 , 40 ]. Significance was accepted at the 5% level ( p < 0.05).…”
Section: Methodsmentioning
confidence: 99%
“…This syndrome differs from other pervasive developmental disorders due to the absence of clinically significant delays in cognitive development, language, adaptive behavior and autonomy. Asperger’s syndrome, first mentioned in DSM-IV [ 1 ], is no longer present in DSM-5 [ 2 , 3 ]; currently, individual situations previously classified as Asperger’s syndrome continue to exist clinically but fall within the level 1 autism spectrum disorders (ASD) [ 2 ]. In the present paper, we use the tag HFA.…”
Section: Introductionmentioning
confidence: 99%
“…These studies contribute to improving people’s understanding of the relationship between somatic and mental symptoms in developmental disorders. It points to common genetic pathways and other potential mechanisms that may be involved ( Dovey et al, 2019 ; Frolli et al, 2021 ). In addition, the simultaneous assessment of medical and psychiatric disorders may be of great value.…”
Section: Introductionmentioning
confidence: 99%